2022
DOI: 10.5455/njcm.20190807124747
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Knowledge, Attitude and Practice Regarding Fami-ly Planning Methods among Women Residing in Peri-Urban Area of Bangalore City

Abstract: Introduction: India is currently facing problems with pre-fix of ‘P’. They are “population explosion”, poverty, and pollution. Population explosion is directly perpetuating the other two problems. Family planning is the only safest and cost effective strategies to have impact on health of women. In many studies it was found that though people were aware of contraceptives but its usage was limited. To know the various factors influencing usage of family planning methods this study was conducted. The study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This was probably because the family planning of choice could have been used to prevent unplanned pregnancies rather than other reasons. These study findings contradict a study by Devaru et al, (2020) which rather reported that 81.42% of the women stopped or did not use contraception because they found it uncomfortable.…”
Section: Practices In Utilization Of Familycontrasting
confidence: 99%
See 1 more Smart Citation
“…This was probably because the family planning of choice could have been used to prevent unplanned pregnancies rather than other reasons. These study findings contradict a study by Devaru et al, (2020) which rather reported that 81.42% of the women stopped or did not use contraception because they found it uncomfortable.…”
Section: Practices In Utilization Of Familycontrasting
confidence: 99%
“…It could also be due to the perception that using contraception would reduce a woman's fertility and that it could help to effectively determine the desired family size. The findings of this study agree with a study by Devaru et al, (2020) which showed that (64.8%) of the women in their study had ever used contraception.…”
Section: Practices In Utilization Of Familysupporting
confidence: 92%
“…These results to much extent agree with the results of a study conducted by Devaru et al where majority of the study subjects had adequate awareness regarding female sterilization, IUCD complications and barrier methods of contraception. 17 The present study results revealed that about 39% of women had poor level of knowledge and very scanty number of women had good level of knowledge regarding family planning. These results are more or less collaborating with the findings of a study conducted by Priyadarshini et al which found that 40% and 43% of study participants had adequate and inadequate knowledge respectively.…”
Section: Discussionmentioning
confidence: 52%
“…According to National Family Health Survey (NFHS 4) (2015-2016), a total of 51.8% of married women use any method of family planning, of which female sterilization accounts for a majority by 48.6%, intrauterine device (IUD) by just 0.8% of women, pills by 0.4%, and condom by 1.3% women. 1 More than 45.5% women undergoing sterilization belong to young reproductiveage group of 20-25 years. 2 The gold standard for recanalization has been microsurgical tubal recanalization through laparotomy.…”
Section: Introductionmentioning
confidence: 99%